Development of Sepak Takraw Sports Management System For private universities in Thailand - Janthamontree, Umnouy (Journal of Management Science Nakhon Pathom Rajabhat University, 2021)
The objective of this research were to (1) study and develop the Sepak Takraw sports management system of private universities in Thailand and (2) evaluate the quality of Sepak Takraw sports management system of private universities in Thailand. Research study model use research and development along with in-depth interviews and focus group discussions. The sample group was administrators, sports teachers and general teachers in 9 private universities, totaling 320 people. Interviews and fucus group, The key informants were 9 private university administrators. The research found that 1. The development of Sepak Takraw sports management system of private universities in Thailand In the overall picture, it is at a high level. And when considering each aspect, it was found that the development of Sepak Takraw sports management system of private universities in Thailand In every level By sorting the average from descending as follows The development of vision strategies has the highest meanings, followed by strategic management. Individual considerations sequential strategic planning and strategy determination are the least average. 2. Sepak Takraw Sports Management System is the gathering of personnel, materials, technology and financial resources needed. Used to enable sports organizations to achieve their goals. Executives may be in the form of individuals. Or the committee is responsible for collecting the resources, personnel, money and tools that will be used to work and achieve goals. Article history: Received 18 April 2019 Revised 20 July 2019 Accepted 23 July 2019 SIMILARITY INDEX = 0.00 %